Evaluation Tool of Land Suitability for Medicinal Plants - Supli Effendi Rahim; Ahmad Affandi Supli; Nurhayati Damiri; Chairil Zaman; Husin Husin (Sriwijaya Journal of Environment, 2019)
Medicinal plants have been very important plants that are responsible in maintaining the health of millions of people in the world  since a very long time. Planting these crops must be carried out on a land that is suitable based on the results of a land suitability evaluation.  A framework to evaluate the land suitability for many land uses is initiated by Food and Agricultural Organization (FAO) in the late 1970’s. As the advent of smart phone nowadays becoming ubiquitous technology to solve problems in most settings, such as education, agriculture, medicine, psychology, and many others. This paper is to capitalize such advantage by converting the framework into a mobile app. This solution is hoped to help land users or planners to be more effective and efficient in evaluating their land. An algorithm is employed in the form the Rule Based System (RBS) in a way to construct the framework into bunch of rules that connect each other, resulting the conclusion of suitability. The rules itself are working on some variables, namely annual rainfall, altitude, drainage, soils’ type, pH, flood risk, fertility of the soils, soil solumn depth, etc. This study focuses on three medicinal crops only, which are candlenut, cardamom and onion to be evaluated. Data of agro climatic that were determining the suitability of the crops were developed into general and specific criteria for the plants. A usability model was studied from 40 respondents using the app. It is found that the usability of the app was in “very good” classification, with dimension scores, ranging from 3.79 and 4.22.